(untitled) (Research, Society and Development, 2020)
This review aimed to compile the results of combined use of vitamin C and E supplementation, their antioxidant effects applied in general diseases, researched in the past years and compare such dosages with the ones separately recommended in Normative Instruction nº 28 published on June of 2018 by the Brazilian National Health Surveillance Agency (ANVISA). Bibliographic research was performed in three databases on combined supplementation and the synergistic relationship between vitamins C and E. The dosages used by the researchers were tabulated for better understanding and the results were discussed and compared against the recommendations established by ANVISA low. In conclusion, when the maximum and minimum daily intake levels of vitamins C and E was drafted in the legislation, according to the population subgroups, ANVISA defined criteria for the designation of antioxidant bioactive compounds and regulated the possibility of combined supplementation of these compounds in reducing the risk of disease through oxidative stress. On the other hand, on the researcher and / or health professional falls the responsibility to previously define the supplementation protocol, considering the synergistic relationship of the constituents and avoiding the generation of pro-oxidant effects, which possibly tends to result in an adverse effect to the desired one.